The Influence of Company Characteristics and The Size of The Sharia Supervisory Board on Islamic Social Reporting - Muhamat Aji Bimatara; Dita Andraeny (ITB AAS INDONESIA Surakarta, 2026)
This study aims to determine the effect of profitability, company size, company age, and the size of the Sharia Supervisory Board on Islamic Social Reporting (ISR). This research is motivated by the importance of transparency and accountability in social reporting, in accordance with Sharia principles, within Islamic financial institutions and by differences in previous research results. This study used a sample of Islamic commercial banks in Indonesia registered with the Financial Services Authority (OJK) for the 2020-2024 period. The population consisted of 14 companies, resulting in 62 unbalanced data sets. The data analysis technique used was panel data regression in EViews 13. The results of this study indicate that profitability, company size, and company age do not significantly influence Islamic Social Reporting (ISR). Meanwhile, the size of the Sharia Supervisory Board has a significant positive effect on Islamic Social Reporting (ISR).